Impact of terminal polar substitution on elastic, electro-optic and dielectric properties of four-ring bent-core nematic liquid crystals. Issue 21 (26th March 2018) - Khan, R. K.; Turlapati, S.; Begum, N.; Mohiuddin, G.; Rao, N. V. S.; Ghosh, S.
Abstract : Here we report the influence of terminal –F, –Cl and –NO2 substitution on the elastic, dielectric and polar switching behavior of four-ring bent-core liquid crystals (LCs). Abstract : Here we report the influence of terminal –F, –Cl and –NO2 substitution on the elastic, dielectric and polar switching behavior of four-ring bent-core liquid crystals (LCs). Elastic constants of nematic liquid crystals are the key parameters in determining the threshold voltage and sensitivity to electro-optical response in a device. The elastic properties of bent-core liquid crystal systems show atypical temperature dependence and there is no hard-core theory to explain the behavior. However based on molecular simulation and atomistic calculations it is found in earlier studies that the bend angle dominates the behavior of elastic constants and the terminal or lateral substitutions have very little effect. Here we have studied three bent-core compounds which are differentiated only by their terminal polar substitution. The bend angle is identical (∼146°) for all the three compounds yet they show dramatically different elastic properties. In the fluoro-substituted compound K 11 > K 33, while for the other two compounds K 33 > K 11 . Thus it is evident that the terminal polar substitution plays vital role in determining the elastic properties of bent-core systems. Correlating the mesophase ranges with the respective dipole moments of the samples it is observed that the fluoro-substituted compound (11-2M-F) with lowest dipole moment favours only nematic phase with smallest mesophase range (46.1 °C), compound 11-2M-Cl with moderate dipole moment favours short range nematic, broad range smectic with moderate mesophase range (53.1 °C), whereas the compound 11-2M-NO2 possesses the widest mesophase range (99.8 °C) with a very narrow nematic and a broad smectic phase amongst the three studied compounds.